Role of magnetic resonance imaging in the diagnosis of cervical lymph node metastasis with unknown primary - Swapnali Y Chaudhary; Varsha B Aher; Rajendra S Birangane (Wolters Kluwer Medknow Publications, 2015)
Visual inspection and bimanual palpation are the cornerstones of diagnosis of diseases of the oral cavity. Clinical examination, however, could underestimate the deep spread of tumors and thereby the submucosal extent and limiting accurate pretreatment staging of disease. Imaging provides additional staging information such as precise location and local extent of the tumor which help in the selection of most effective treatment option and extent of surgical excision. Magnetic resonance imaging (MRI) offers an excellent aid for the evaluation of tumors of the oral cavity due to direct visualization of soft tissue in multiple planes. An interesting case of a 35-year-old male patient with extensive lymph nodal mass involving left side of the neck with limited mouth opening is reported. MRI was very helpful in locating the site of primary neoplastic mass along with providing the exact extent of the tumor and its effect on adjacent vital structures.